Measuring psychological and physiological stress in emergency clinicians. (March 2021) - Merrick, Eamon; Busby Grant, Janie; Mckune, Andrew; D'cunha, Nathan; Murphy, Elizabeth; Naumovski, Nenad; Fry, Margaret
Abstract: Background: Evidence regarding stress, team structure and decision-making has been used to inform efficacious team composition and deployment. There have been limited attempts to establish the relationship between psychological stress with physiological data within professional environments. The current study explored measures of psychological and physiological stress in Australian emergency practitioners. Methods: Thirty-seven staff in an Australian emergency department completed an online survey assessing freedom to make decisions, social support, and psychological job demands. Seven participants provided saliva samples three times daily for seven days (valid n = 141 samples). Cortisol levels of the samples were analysed using competitive enzyme immunoassay kits, and α-amylase using kinetic enzyme assay kits. Results: Years of emergency experience was positively associated with freedom to make decisions, and social support was negatively correlated with psychological demand. No consistent pattern was observed between cortisol level and reported psychological demand, decision freedom or social support. Physical activity was not reflected in elevated α-amylase. Diurnal variation of cortisol and α-amylase was not affected by shiftwork. Conclusions: The data supports the case for using multiple assessments to measure stress. While the psychological data is consistent with previous findings, there are possible disparities between psychological reports and physical indicators of stress.